The typographic layout of school course books of the Lviv publishing house of Kazimierz Stanisław Jakubowski (1868–1926) - Gruchała, Irena (Folia Toruniensia, 2017)
The research on the book includes all the aspects of its life – manufacture, distribution and use. From the 16th century the typographic resources of printing houses became standardized. Thus, the author suggested that the analysis should apply to only one kind of publication and focus on its cover, typographic layout, illustrations, publishing framework. This subject matter is rarely addressed by authors as a separate problem. This article is a minor contribution to the history of editing of a strictly defined form of a book. It discusses the typographic and editing layout of school course books published by the bookshop of Kazimierz Stanisław Jakubowski. It was set up in Lviv at the end of the 19th century. The job of a printer and a publisher was often performed by one person. Course books printed and published by Jakubowski were highly valued by contemporary users. The article presents the findings of the analysis of 61 course books. The research confirms that printing houses of the time had rich typographic resources. The publications included various fonts of print, invariably adjusted to the age and abilities of the student. Various styles were applied in the edition of prosaic and poetic texts. Elements of the page were carefully planned. Wide margins, interline spacing and the so called empty lines left much space free of print, which facilitated reading. Another good point of the publications was the transparent division of the text into smaller units and precise distribution of headlines. Among elements of the publishing framework there are various appendices. Books were adorned with numerous illustrations, mostly black and white. The above-mentioned factors and the fact that this reliable editor cooperated with outstanding authors contributed to the fact that books published by Jakubowski were highly valued.